Prevalence of primary adrenal insufficiency in patients diagnosed with tuberculosis at the Dr George Mukhari and Kalafong hospitals in South Africa - Broodryk, Jaco (University of Limpopo (Medunsa Campus), 2010)
Objectives: Tuberculosis (TB) is a major health problem in South Africa with disease rates more than double those observed in other developing countries and up to 60 times higher than those currently seen in the USA or Western Europe. Seventy years ago, it was demonstrated that approximately 70% of patients with primary adrenal insufficiency (PAI) was due to TB and this remains a major cause of PAI in developing countries. With these figures in mind it is of great concern that patients with TB are not screened for adrenal insufficiency more often. The aim of the study was to investigate the prevalence of adrenal insufficiency in patients diagnosed with TB. Study population: Seventy three patients at the Dr George Mukhari- and Kalafong hospitals in Gauteng, South Africa, aged 20-91 years, were included. 49 Females and 24 males were recruited. All patients had positive TB microscopy. Metods: High dose adrenocorticotropic hormone (ACTH) stimulation tests were done on all patients, a post stimulation cortisol concentration of > 500nmol/L was considered a normal response. Baseline ACTH determination was also done on all patients. ACTH determination was performed using the Siemens Immulite 2000 ACTH assay, whilst cortisol determination was done on a Beckman Coulter UniCel DxI 800 immunoassay system. Results: 68 patients had a normal response. 5 patients had a post ACTH stimulation cortisol of less than 500nmol/L. Conclusion: Five patients (6.85%) had a blunted response to the ACTH stimulation test which identifies some form of adrenal insufficiency. None of the patients had an increased ACTH concentration. This finding excludes PAI and the normal ACTH concentrations in these 5 patients are highly suggestive of secondary-or tertiary adrenal insufficiency.
Thesis (M Med(Chemical Pathology))--University of Limpopo (Medunsa Campus), 2010.
Keywords: Tuberculosis; Tuberculosis|xdiagnosis